How including ecological realism impacts the assessment of the environmental effect of oil spills at the population level: The application of matrix models for Arctic Calanus species. (October 2018) - de Vries, Pepijn; Tamis, Jacqueline; Hjorth, Morten; Jak, Robbert; Falk-Petersen, Stig; van den Heuvel-Greve, Martine; Klok, Chris; Hemerik, Lia
Abstract: For oil spill responses, assessment of the potential environmental exposure and impacts of a spill is crucial. Due to a lack of chronic toxicity data, acute data is used together with precautionary assumptions. The effect on the Arctic keystone (copepod) species Calanus hyperboreus and Calanus glacialis populations is compared using two approaches: a precautionary approach where all exposed individuals die above a defined threshold concentration and a refined (full-dose-response) approach. For this purpose a matrix population model parameterised with data from the literature is used. Population effects of continuous exposures with varying durations were modelled on a range of concentrations. Just above the chronic No Observed Effect Concentration (which is field relevant) the estimated population recovery duration of the precautionary approach was more than 300 times that of the refined approach. With increasing exposure concentration and duration, the effect in the refined approach converges to the maximum effect assumed in the precautionary approach. Highlights: Population models are set up for two Arctic Calanus spp. Toxic effects of oil on model parameters are included based on theoretical approach. Recovery is compared using a precautionary and full dose-response approach. Just above the NOEC the ratio between the two approaches can be more than 300. This indicates the level of conservatism used in oil spill response.